Pengaruh Enterpreneurial Leadership Terhadap Employee Performance Di Lapas Kelas IIA Purwokerto - Brilian Pradipta; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
This article discusses the relationship between the influence of entrepreneurial leadership on employee performance. This is motivated by the hypothesis that entrepreneurial leadership affects employee performance. This study aims to examine and analyze the role of entrepreneurial leadership as a moderator of employee performance. The research was conducted on employees at Class IIA Purwokerto Prison using quantitative methods. The number of employees in Class IIA Purwokerto Lapas is 125 people, 35 employees were taken as a sample. The data is processed using the SPSS program. The results of data analysis show that entrepreneurial leadership influences employee performance